Peningkatan Kinerja Modul PV Kanopi dengan Optimasi Pembayangan pada Area Terbatas - Friansa, Koko; Pradipta, Justin; Haq, Irsyad Nashirul; Leksono, Edi; Ariwibawa, Kristiawan (Majalah Ilmiah Teknologi Elektro; Vol 21 No 1 (2022): (Januari - Juni) Majalah Ilmiah Teknologi ElektroDO - 10.24843/MITE.2022.v21i01.P07, 2022)
In this paper, the contribution for finding the tilt and azimuth angle, location, and shift optimum with shading analysis method using PVSyst software has been done. The PV module capacity is 20 kWp that and integrated as canopy in the crosswalk between LABTEK V and LABTEK VI, ITB campus, Bandung. Coodinate from the location of PV modules is 6,89 LS dan 107,61 LT (- 6,89 o S, 107,61 o E). Fixed tilt was used for the PV modules orientation. The buildings and trees around the PV module cause shading effect in the PV modules, therefore, to maximize PV performance additional optimization and shading analysis have to be carried out. Performance achieved tilt angle 11 o and azimuth 0 o with effective global irradiation 1160,1 kWh/m2/year and energy array 21,75 MWh/tahun. After tilt optimization, shift and array optimization was added for improve the PV modul performance. In the added the shift and array optimization scenarios, the effective global irradiation has improved 72 kWh/m2/year and 14,9 kWh/m2/year respectively and the energy array has improved 1,26 MWh/year and 0,25 MWh/year.